Analisis pengaruh kecemasan matematika terhadap self-efficacy pada siswa SMA - Dian Aliza Pratidina; Aziz Muhtasyam; Syifaurrohmah Kusuma Edy; Yuli Ismayanti (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
This study aims to determine whether mathematical anxiety affects high school students' self-efficacy. Based on the opinion expressed by Pajares and Kranzler (Watts, 2011) math self-efficacy and mathematical anxiety have a negative correlation, which means that high math anxiety is related to low math self-efficacy, or vice versa. This type of research is quantitative using a survey method. The population in this study were high school students in Banten, the research sample was class X high school students at SMAN 1 Waringinkurung, SMAN 8 Kota Serang, SMAN 1 Tirtayasa, and MAN 2 Pandeglang. The sampling technique used quota sampling method. Mathematical anxiety and self-efficacy instruments use a questionnaire that has good validity and reliability with a loading factor value for all indicators that is more than 0.5 and a construct reliability value that is more than 0.7. The results showed that math anxiety had a negative direct effect on self-efficacy of -0.33, meaning that there was a significant negative relationship between math anxiety and self-efficacy, meaning that the lower the student's mathematical anxiety, the higher the student's self-efficacy level and vice versa.